A communication protocol between community pharmacists and primary care professionals to solve patients´ medication problems - Ainhoa Oñatibia-Astibia; Belen Larrañaga; Josune Iribar; Arritxu Etxebarria; Nekane Odriozola; Miguel Ángel Gastelurrutia; Ana Bustinduy; Estibaliz Goyenechea (International Journal of Integrated Care, 2019)
Introduction: Communication between health professionals (HP) is a key issue to enhance quality and efficiency of health care system. (1,2). Community pharmacists (CPs) are often not integrated in the current HP communication model. Therefore, it is necessary to enhance communication between HP. Practice change implemented: A pilot study was performed between the 18 community pharmacies and the 10 primary care centres of Donostialdea Integrated Healthcare Organisation (IHO). It was extended to all community pharmacies of Donostia/San Sebastian interested in participating (n=60). CPs identify a problem in patients´ medication that requires communication with primary care professionals (PCP). CPs contacted with the customer service area by telephone for urgent problems and by email for not urgent problems. The customer service area derivate the problem to the primary care doctor, primary care nurse or to the social service responsible. Aim: To implement communication channels with agreed protocols to solve different situations related to patients´ medication that require communication with PCP of Donostialdea IHO. Population: Elderly patient that attends to the community pharmacy and the CPs detects a medication problem that requires communication with PCP. CPs, primary care doctor, primary care nurse, social services and customer service area. Timeline: Before the launch of the project, PCP of Osakidetza, Official Pharmacist Association of Gipuzkoas´ pharmacist and community pharmacist of Donostia agreed the protocol. A 6-month pilot study with 15 community pharmacies was conducted between March-August 2017. The main study including 60 community pharmacies started in March-2018 till February-2019. In August-2018, the first 3-month reports have been analysed. By April-2019 definitive results will be presented. Highlights: During the pilot study, 370 problems (87.8%) out of 421 were solved and during the main study, 275 problems (87.8%) out of 313. Email was the most used way (n=239,76.4%). The most prevalent incidence was that patient did not have available the electronic prescription (n=232,74.1%). HP´s satisfaction was high and the it was noticed as an effective way to solve problems. Sustainability: The communication system is used continuously over the time. The majority of medication related problems are solved with non-costly resources. Transferability: Once obtained the final results, it could be implemented in other IHO of the Basque Country. Conclusions: The communication channel between CPs and PCP is an efficient way to solve different situations that happen in community pharmacies and avoids problems such as difficulty of pharmacists on getting in touch or interruption of PCPs´ daily practice. Discussion: Implementing a communication protocol between CPs and PCP is necessary due to the number of incidents that are solved. The use of a single contact point for CPs, is empathised since it does not interrupt the daily work of the HP and it does not mean a difficult and lengthy process for the CPs. Lessons learned: In order, the enrolment of the different HP when designing the protocol and an adequate training of the professionals involved, is a main issue to establish and maintain a communication protocol between CP and PCP